Thoracoscopic repair of type C oesophageal atresia in a Nigerian hospital: A report of two cases - Arua Obasi Igwe; Lakmeel Kannachamkandy; Ebere Lilian Agwu; Temitope A Lawal; Temilolu O Nwankpele; Arinzechukwu O Mosanya; Nikoloz Dzagnidze; Augustine Jeremai Olugbemi; Ibukun Abidoye; Andriy Danyltsiv (Wolters Kluwer Medknow Publications, 2024)
Management of oesophageal atresia (OA) with tracheoesophageal fistula (TOF) in Nigeria and the West African subregion has no doubt been a very demanding task for paediatric surgeons, not necessarily due to lack of skills, but due to the significant demand on neonatal intensive care, which in our region, is often fitted with the poor infrastructure needed to make this a success. Furthermore, the use of open thoracotomy has increased this demand resulting in a significant number having severe morbidities and significant mortality rates. Hence, in our subregion, there is still a slow progression to meet up with the evolving trend of the management of this complex condition in the developed world. Following the first documented successful thoracoscopic repair of OA with TOF since 2000, there has been a progressive evolution and refinement of this technique, such that thoracoscopic repair is fast becoming the gold standard for the repair of all types of OAs, including long-gap anomalies. This article reports our experience with the first two cases of thoracoscopic repair of OA with TOF in the West African subregion.